2020
DOI: 10.3389/fpsyg.2020.607274
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment and Sociometric Status in Primary Education: Gender Differences

Abstract: The acceptance or rejection of classmates is one of the most widely recognized determinants of wellbeing in childhood. This study analyses psychosocial adjustment and sociometric status in primary education pupils, and possible differences by gender. A cross-sectional survey was undertaken in Huelva (Spain). The surveyed schools were selected using a stratified random sampling technique with both public and private elementary schools. Sample was composed of 247 4th grade students. Data revealed gender differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
4
0
3
Order By: Relevance
“…Lo antes señalado, es evidenciado en la investigación de Esparza-Reig et al ( 2021), en donde se señala que las mujeres poseen mayores grados de conducta prosocial en comparación con los hombres. En el mismo sentido, los hallazgos de esta investigación son similares en relación a lo expuesto por Atkinson et al (2021), Muñoz-Silva et al (2020 y Van Lange et al ( 2018), de las cuales emergen nuevas consideraciones que pueden enriquecer este trabajo, producto del reconocimiento de las interacciones entre factores socio-genéticos y las conductas prosociales.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Lo antes señalado, es evidenciado en la investigación de Esparza-Reig et al ( 2021), en donde se señala que las mujeres poseen mayores grados de conducta prosocial en comparación con los hombres. En el mismo sentido, los hallazgos de esta investigación son similares en relación a lo expuesto por Atkinson et al (2021), Muñoz-Silva et al (2020 y Van Lange et al ( 2018), de las cuales emergen nuevas consideraciones que pueden enriquecer este trabajo, producto del reconocimiento de las interacciones entre factores socio-genéticos y las conductas prosociales.…”
Section: Discussionunclassified
“…Bajo esta perspectiva, los profesores universitarios se encuentran llamados a trascender su clásica definición como transmisores del conocimiento hacia una redefinición de sus alcances: el gobierno de instituciones altamente complejas, la gestión de situaciones multicausales y el liderazgo de la formación integral de sus estudiantes, podrían instalar valores como la empatía y solidaridad configurando un comportamiento ético y socialmente responsable en los actuales estudiantes y futuros profesionales (Severino-González et al, 2021b); esto no podría ser posible sin la concepción de una docencia para el bien común, la transparencia y el altruismo, logrando impactar virtuosamente en la formación, gestión, extensión, investigación y participación ciudadana tanto de educandos y docentes (Muñoz-Silva et al, 2020). Desde la visión de la neurociencia informacional, tal relación solo puede sostenerse desde un paradigma neguentrópico en donde las habilidades socialmente responsables alcancen los tres componentes de la conciencia, los subsistemas: afectivo, cognitivo y conativo.…”
Section: Introductionunclassified
“…A T -test revealed that boys had significantly higher hyperactivity/inattention scores compared to girls, t (50) = 3.01, p = 0.005. Other studies also found gender differences in children’s prosocial behavior and behavioral problems assessed using the SDQ ( Muñoz-Silva et al, 2020 ). Child gender was also significantly correlated with one dimension of the moderator variable ( r = −0.28, p = 0.04).…”
Section: Resultsmentioning
confidence: 86%
“…Although gender differences in oppositional behavior is not certain, conduct problems such as aggression can be more common among boys ( 43 , 44 ). Furthermore, gender difference in psychosocial adjustment was found particularly in terms of prosocial behavior in girls and behavioral problems in boys ( 45 ). Some studies have reported that female gender can correlate with anxiety and depression ( 46 , 47 ), while others don't find any gender differences ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%